Development of a double-monitoring method for the determination of total antioxidant capacity as ascorbic acid equivalent using CUPRAC assay with RP-HPLC and digital image-based colorimetric detection - Borahan, Tulay; Girgin, Ayca; Atsever, Nihan; Zaman, Buse Tugba; Chormey, Dotse Selali; Bakirdere, Sezgin (SPRINGER, 2022)
This study was aimed at developing a double-monitoring detection system for measuring the TAC (total antioxidant capacity) of apple juice samples. The conventional CUPRAC (cupric ion reducing antioxidant capacity) assay was coupled to high-performance liquid chromatography-ultraviolet (HPLC-UV) and digital image-based colorimetric detection systems. In the CUPRAC assay, a chromogenic copper(II)-neocuproine (Cu(II)-Nc) reagent was used to oxidize the antioxidants, which is further reduced by the antioxidants to a yellow-colored copper(I)-neocuproine (Cu(I)-Nc) chelate having maximum absorption at 450 nm. The yellow-colored samples were measured by HPLC-UV and digital image-based colorimetric detection systems. Parameters of the HPLC-UV system were optimized to obtain a sharp and transient peak at 450 nm analytical wavelength. Under the optimum experimental conditions, the detection limits calculated for ascorbic acid using the HPLC-UV and digital image-based colorimetric detection systems were 0.28 and 0.70 mg/L, respectively. Satisfactory results (95.6-102%) were calculated for apple juice samples spiked at different concentrations for both detection systems, and very low (< 5.0%) percent relative standard deviation values were recorded. The TAC value for ascorbic acid equivalent in apple juice sample was found as 131 +/- 0.1 mg/L using the HPLC-UV system.
Keywords: CUPRAC; HPLC-UV; Ascorbic acid; Smartphone; Digital image; Apple juice; Food Science & Technology